IMR 665: Management of Audio Visual Records & Archives. Individual assignment: Article summary / Wan Muhammad Zulaili Wan Mat - Wan Mat, Wan Muhammad Zulaili (2015)
Article on: Article 1 - “The conservation and preservation of film and magnetic materials (2) magnetic materials” Article 2 - “The public-private partnership case study in digitization of audiovisual heritage”